THE EFFECT OF LIQUIDITY RATIO, SOLVENCY RATIO, AND PROFITABILITY RATIO ON FINANCIAL DISTRESS - Putri Khairunnisa, Dellavitrya; Muhammad Zakaria Hakim, Heikal (The Double Entry Journal, 2024)
Retail trade sub-sector companies are one of the industries that are very close to us. However, the retail industry has experienced many ups and downs, especially since the presence of e-commerce and the pandemic of covid-19. This study aims to determine the effect of liquidity ratio, solvency ratio and profitability ratio on financial distress, especially in retail trading subsector companies listed on the Indonesia Stock Exchange in 2017-2021. The research method uses a verificative descriptive method. The population of this study is Retail Trading Subsector Companies Listed on the Indonesia Stock Exchange in 2017-2021. The samples used were 10 companies from a total of 36 companies taken using purposive sampling techniques. The data analysis methods used in this study are classical assumption test, multiple linear regression analysis, determination coefficient, partial test (t-test) and simultaneous test (F-test). The results of this study show that the Liquidity Ratio has a partial effect on financial distress, the Solvency Ratio has a partial effect on financial distress, the Profitability Ratio has a partial effect on financial distress as well as the Liquidity Ratio, Solvency Ratio and Profitability Ratio simultaneously affect on financial distress.